2018
DOI: 10.5114/aoms.2018.72242
|View full text |Cite
|
Sign up to set email alerts
|

How does the activity level of the parents influence their children’s activity? The contemporary life in a world ruled by electronic devices

Abstract: IntroductionApart from many positive changes associated with technical civilization, there are also – from the health point of view – some threats. The reduction in the level of physical activity is one of them. The aim of the study was to investigate whether there are any relationships between children’s physical activity and behaviors, and to assess the impact of the adults’ activity on their children’s habits.Material and methodsThe study involved a group of 340 children aged 7–12 years (mean age: 9.81 ±1.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Currently, adolescents spend many hours using electronic devices, so at an earlier age the example and influence of physically active parents is greater and has more effect [16], especially if we want PA to be perceived positively and generate adherence [82][83][84], and even more taking into account the important influence that the peer group has on PA practice by adolescents [85]. Consequently, it is important to make parents see that the support they provide to their children is essential to generate adherence to PA practice, being aware that such influence may appear in different ways [58].…”
Section: Final Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, adolescents spend many hours using electronic devices, so at an earlier age the example and influence of physically active parents is greater and has more effect [16], especially if we want PA to be perceived positively and generate adherence [82][83][84], and even more taking into account the important influence that the peer group has on PA practice by adolescents [85]. Consequently, it is important to make parents see that the support they provide to their children is essential to generate adherence to PA practice, being aware that such influence may appear in different ways [58].…”
Section: Final Synthesismentioning
confidence: 99%
“…Currently, parental support acquires greater relevance since adolescents invest a lot of time every day using screen devices [16], a circumstance that is aggravated when both parents act as a negative example, also making excessive use of these devices and having a sedentary leisure [17]. Although parental support is essential in both genders, it seems that maternal modeling of healthy habits has a greater influence on children compared to paternal modeling [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Our most salient finding was that parental attitudes and PA patterns could predict an adolescent’s PA level. A growing body of literature has identified that parents have a large influence on adolescent PA levels [ 14 , 15 , 26 ]. Parents have the potential to provide encouragement, modeling, and tangible support in order to promote PA to their child [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the modern civilized world of expansion of mechanization and electronics, children and adolescents from the earliest years spend free time choosing sitting position (in front of TV/computer). Lacking physical activity leads to muscular misbalance, which can be a risk factor for disorders in body posture [27, 28]. On the other hand the continual bearing of heavy school bags imposes additional tension on the developing spine of children, making it more disposed to postural deviations and finally back complications [29, 30].…”
Section: Discussionmentioning
confidence: 99%